Zoogeography of Arachnida - Beron, Petar (Monographiae Biologicae, 2018)
This volume merges all geographical and paleogeographical data on all groups of the arachnofauna. The book features topics such as the ecological factors, climate and other barriers that influence the distribution of arachnida. It also elaborates on the characteristics of the distribution such as arachnida at high altitude (e.g. Himalaya), in caves, in polar regions and highlights differences between the arachnofauna of e.g. Mediterranean regions vs Central Europe, West African vs Indomalayan and more. Furthermore, amongst other topics the volume also includes chapters on the systems of arachnida, fossil orders, dispersal and dispersion, endemics and relicts, regional arachnogeography, cave and high altitude arachnida.